The Impact of Social Media Analytics on SME Strategic Decision Making - Nugroho, Dimas; Angela, Putri (Pandawan Sejahtera Indonesia, 2024)
In the digital age, the emergence of social media has transformed the operational landscape of small and medium enterprises (SMEs). Recognized as a tool that generates comprehensive insights, social media analytics supports strategic decision-making. However, the concrete impact of social media analytics on strategic decisions in SMEs still requires further exploration. This study aims to assess the impact of social media analytics on strategic decision-making in SMEs, considering mediating variables such as organizational innovation and adaptability. Employing Structural Equation Modeling (SEM) with SmartPLS 4.1 software, the study analyzed data collected from 200 SMEs actively using social media for operations and marketing. The findings reveal that social media analytics significantly enhances organizational innovation and adaptability, which in turn positively affects strategic decision-making. This analysis underscores the importance of social media as a strategic resource in a dynamic business environment. The study provides valuable insights for SME owners on the critical role of social media analytics in enhancing strategic decisions. Theoretically, it extends the literature on social media analytics and strategic management within the SME context. Practically, the results serve as a foundation for SMEs to integrate social media analytics technology into their decision-making processes, thereby boosting adaptability and innovation in their operations.